2016
DOI: 10.4049/jimmunol.1500710
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Capped Lipoarabinomannan from Mycobacterium tuberculosis Induces CD4+ T Cell Anergy via GRAIL

Abstract: Mycobacterium tuberculosis cell wall glycolipid, Lipoarabinomannan, can inhibit CD4+ T cell activation by down-regulating phosphorylation of key proximal TCR signaling molecules Lck, CD3ζ, ZAP70 and LAT. Inhibition of proximal TCR signaling can result in T cell anergy, in which T cells are inactivated following an antigen encounter, yet remain viable and hyporesponsive. We tested whether LAM-induced inhibition of CD4+ T cell activation resulted in CD4+ T cell anergy. The presence of LAM during primary stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 55 publications
1
40
0
1
Order By: Relevance
“…The medium was changed on days 5 and 7 of culture, and macrophages were used on day 8. CD4 + T cells were isolated from spleens as described previously (27, 29). Spleens were dissociated through a 40-µm screen in 5 ml DMEM, and red blood cells were lysed in ACK lysis buffer (150 mM NH 4 Cl, 10 mM KHCO 3 , 0.1 mM Na 2 EDTA, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The medium was changed on days 5 and 7 of culture, and macrophages were used on day 8. CD4 + T cells were isolated from spleens as described previously (27, 29). Spleens were dissociated through a 40-µm screen in 5 ml DMEM, and red blood cells were lysed in ACK lysis buffer (150 mM NH 4 Cl, 10 mM KHCO 3 , 0.1 mM Na 2 EDTA, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were activated for 24 h with plate bound anti-CD3ε (1 µg/ml) and soluble anti-CD28 (1 µg/ml) in the continued presence of vesicles or LAM; supernatants were harvested, and IL-2 was quantitated by ELISA using the murine IL-2 DuoSet (R&D Systems, Minneapolis, MN). Alternatively, T cells were activated as above for 48 h, and proliferation was measured as described (29) by addition of 1 µCi of [ 3 H]-thymidine/well (Amersham Pharmacia Biotech, Piscataway, NJ) for an additional 16 h. [ 3 H]-thymidine incorporation was measured by liquid scintillation counting. Results were expressed as mean cpm of triplicate values +/− SD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, extracellular Mtb MVs may traffic to and subsequently impair the antigen presentation capacity of uninfected macrophages in the lung. The second mechanism is based on the observation that purified Mtb LAM inhibits TCR signaling and CD4+ T cell activation (Mahon et al, 2012; Sande et al, 2016) and that extracellular LAM is secreted via MVs from Mtb-infected cells (Athman et al, 2015). Our recent work demonstrates that Mtb MVs are enriched for LAM, inhibit T cell activation more potently than purified LAM, and induce T cell anergy (Athman et al, manuscript in revision).…”
Section: Mycobacterium Tuberculosis Membrane Vesiclesmentioning
confidence: 99%
“…Earlier studies from his group have shown that Mtb through prolonged activation via TLR2 inhibits MHC-II Ag processing and presentation in macrophages [20]. He discussed more recent studies demonstrating that Mtb lipoarabinomannan (LAM) and lipomannans (LM) are released in bacterial microvesicles from infected macrophages and can directly inhibit proximal TCR signaling, and induce CD4+ T cell anergy [21,22]. These mechanisms most likely occur during the effector phase of the T cell response and may be relevant to the inability of T cells to clear Mtb during primary infection and during latent infection in lung granulomas.…”
Section: Session I: Early Infection Events and The Biological Consmentioning
confidence: 99%